Analisis Usability Aplikasi Perpustakaan Nasional Melalui Pendekatan Heuristic Evaluation Berbasis Human Computer Interaction - Randy, Muhammad Randy Fachrezi; Hafiz Aryanda; Muhammad Farhan; Dimas Aqila Aptanta; Arief Denis Walidein (Universitas Harapan Bangsa, 2025)
Rapid advancements in technology have driven the emergence of various digital applications, including digital libraries. One such application is iPusnas, which serves as a digital literacy platform among users. Based on user reviews of the Play Store, many users have reported issues such as the app’s slow responsiveness and non-functional filters, such as the inability to sort alphabetically. These problems indicate a potential deficiency in the usability of an application. Therefore, a usability evaluation is needed to determine the extent to which iPusnas adhere to the principles of Human-Computer Interaction (HCI). The method employed is Jakob Nielsen’s Heuristic Evaluation, which assesses ten usability principles, including consistency, error prevention, and minimalist design. The evaluation was conducted by five internal evaluators, using a severity rating scale ranging from 0 to 4. The results show that iPusnas continue to experience usability issues in several areas, particularly in the principles of Help and Documentation (4.00), Flexibility and Efficiency of Use (3.33), and Visibility of System Status (3.13). The principle of Error Prevention received the lowest severity score (1.20), suggesting that it functions relatively well. This study underscores the effectiveness of multi-evaluator heuristic evaluation in identifying application issues, and serves as a foundation for future improvements aimed at enhancing user satisfaction.